2023
DOI: 10.1097/aco.0000000000001247
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric pain management: from regional to virtual

Abstract: Purpose of reviewDue to increased interest in opioid-sparing multimodal analgesic strategies both inside and outside of the operating room, anaesthesiologists have started to look towards regional anaesthesia as well as nonpharmacological pain-reducing techniques. The purpose of this article is to discuss current trends and recent developments in regional anaesthesia and virtual reality for paediatric pain management.Recent findingsThe development of novel fascial plane blocks has expanded regional options for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Improved multimodal efforts for analgesia, including topical anesthesia, neuromodulatory and thermomechanical devices for labs and intravenous access, sucrose and/or breastfeeding as an analgesic aid, comfort positioning, and age-appropriate distraction have shown to have benefits for minor procedures. In addition to multimodal pharmacologic approaches, nonpharmacologic modalities, such as physical therapy, occupational therapy, psychology, and psychiatry, and integrative therapies, such as acupuncture and massage, are very helpful in some patients 144–146 …”
Section: Pediatric Perioperative Pain Management Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…Improved multimodal efforts for analgesia, including topical anesthesia, neuromodulatory and thermomechanical devices for labs and intravenous access, sucrose and/or breastfeeding as an analgesic aid, comfort positioning, and age-appropriate distraction have shown to have benefits for minor procedures. In addition to multimodal pharmacologic approaches, nonpharmacologic modalities, such as physical therapy, occupational therapy, psychology, and psychiatry, and integrative therapies, such as acupuncture and massage, are very helpful in some patients 144–146 …”
Section: Pediatric Perioperative Pain Management Expertisementioning
confidence: 99%
“…In addition to multimodal pharmacologic approaches, nonpharmacologic modalities, such as physical therapy, occupational therapy, psychology, and psychiatry, and integrative therapies, such as acupuncture and massage, are very helpful in some patients. [144][145][146] Acute and chronic pain management in pediatric patients is dynamic and complex; dedicated pediatric pain services targeting a combination of acute, chronic, acute-on-chronic, procedural, or palliative pain needs are essential in centers with significant pediatric patient populations. In any center performing pediatric regional anesthesia, staff with expertise in risk stratification, block placement, catheter management, and pediatric-specific pain management should be present.…”
Section: Pediatric Perioperative Pain Management Expertisementioning
confidence: 99%
“…According to Collins (2023), in children with severe pain and disability, intensive interdisciplinary pain management might be required to improve pain and function [10]. Heydinger et al (2023) have reported that regional anesthesia and virtual reality are valuable tools that serve to relieve pain in children [11]. Lalloo et al have recently published an article that shows that Project ECHO ® (Project Extension for Community Healthcare Outcomes) is a feasible model for the virtual education of interprofessional healthcare providers in treating pediatric pain [12].…”
mentioning
confidence: 99%